Feminine Mystique Presented by The Main Female Character in The Novel Dominicana - Dewi, Cahyanita Pramestya (English Literature Study Program, 2023)
Women are often deprived of their rights based on sexual orientation, gender identity, or sex characteristics. Betty Friedan thinks patriarchal culture makes women too passive, do not think independently, and do not work for themselves. In addition, women are often trapped in feminine mystique, meaning that they are only fixated on the demands of serving their husbands and doing domestic chores. The novel Dominicana by Angie Cruz talks about Ana (the main female character) trapped in a feminine mystique. That novel is the primary source of data in this study. The aims are to find out how feminine mystique is presented in the novel and explain Ana's efforts to get out of these issues. The researcher uses a feminist literary criticism as an approach and applies Betty Friedan's feminine mystique theory. Thus, the results of this study indicate that Ana did not get her rights as a woman and only did domestic chores without having access to public sphere. Therefore, she made various efforts, such as against her husband, finding a part-time job, joining an English class, and revealing her husband's affair. However, the researcher only focuses on the main female character, to discuss the Feminine Mystique that she experiences and the resistance she does. In future research, the researcher hopes that many will analyze this novel as an object of study in literary criticism. Many literary criticism theories and approaches can be used to analyze this novel, such as psychoanalysis, historicism, structuralism, and sociology of literature. Future researchers can also examine this novel with the same approach by choosing different theoretical references.